A Cryoprotectant-Gel Composite Designed to Preserve Articular Cartilage during Frozen Osteoarticular Autograft Reconstruction for Malignant Bone Tumors: An Animal-Based Study. (August 2022) - Chen, Chao-Ming; Chen, Yi-Chun; Wang, Jir-You; Chen, Cheng-Fong; Chao, Kuang-Yu; Wu, Po-Kuei; Chen, Wei-Ming
Objective: We designed a highly adhesive cryoprotectant-gel composite (CGC), based on regular liquid-form cryoprotectant base (CB), aiming to protect cartilage tissue during frozen osteoarticular autograft reconstruction for high-grade sarcoma around the joint. This study aimed to evaluate its effectiveness in rat and porcine distal femur models. Design: Fresh articular cartilage samples harvested from distal rat and porcine femurs were divided into 4 test groups: untreated control group, liquid nitrogen (LN) freezing group, LN freezing group pretreated with CB (CB group), and LN freezing group pretreated with CGC (CGC group). Microscopic and macroscopic evaluation of cartilage condition, TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) assay, and apoptotic protein analysis of chondrocytes were performed to confirm our results. Results: In the rat model, CGC could prevent articular cartilage from roughness and preserve more proteoglycans when compared with the LN freezing and CB groups. Western blot analysis showed CGC could prevent cartilage from LN-induced apoptosis supported by caspase-3/8 apoptotic signaling cascade. Macroscopically, we observed CGC could reduce both articular clefting and loss of articular luminance after freezing in the porcine model. In both models, CGC could reduce articular chondrocytes from degeneration. Fewer TUNEL-positive apoptotic and more viable chondrocytes in cartilage tissue were observed in the CGC group in our animal models. Conclusion: Our study proved that CGC could effectively prevent cartilage surface and chondrocytes from cryoinjury after LN freezing. Freezing articular cartilage surrounded with high concentration of CGC can be a better alternative to preserve articular cartilage during limb salvage surgery for malignant bone tumor.